LEGALITY OF THE PUBLIC PROSECUTOR'S ACCUSATIONS REGARDING THE VERDICT OF CRIME OF CORRUPTION IN THE PALU STATE COURT - Moh. Sabrang; Syamsul Haling; Samsuria (Indonesian Research Journal in Legal Studies, 2023)
The formulation of the general prosecutor's indictment for the criminal act of corruption against fishing boats in Tolitoli Regency did not meet the formal requirements and material requirements which required careful, clear and complete details about the qualifications of the perpetrators (plegen, doen plegen, uitlokker) and the actions committed by the suspects (act) so that the prosecutor's charges become obscure (abscurs libels). Analysis of the texts proves that there is no correlation between the text, the meaning of the text and the context which qualifies the criminal acts alleged by the public prosecutor against the alleged perpetrators of corruption. In order to prevent formal cancellation of the indictment by the court, the public prosecutor in preparing the indictment must include a clear, accurate and complete description of the actions committed and not related to each other, incomplete and partial, especially material requirements so that the description of the public prosecutor is vague/obscure (obscuur libel) so that the charges are null and void and the court's decision is acquitted.